KEMAMPUAN BERBICARA MELALUI METODE SHOW AND TELL PADA SISWA KELAS IV SEKOLAH DASAR - Kilo, Nurcahayani Usman; Husain, Rusmin; Pulukadang, Wiwy T.; Halidu, Salma; Katili, Sukri (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
This research aims to improve the speaking skills of fourth-grade students at SDN 1 Telaga, Gorontalo Regency, through the technology-assisted Show and Tell method. The problems faced include difficulties in pronunciation, flat intonation, inappropriate word choices, and a lack of facial expressions and eye contact. The dominant lecture method resulted in students rarely practicing speaking. Therefore, the integration of technology such as interactive media, video recordings, and digital learning applications was implemented to increase student participation. This research used the Classroom Action Research (CAR) method with data collection techniques through observation, tests, and documentation. The research subjects consisted of 20 fourth-grade students. The results showed that students' speaking skills improved gradually. In the initial observation, only 3 students (15%) had good speaking skills. After Cycle I, this number increased to 50%, and in Cycle II, it reached 85%, meeting the success indicators. The conclusion of this study indicates that the technology-assisted Show and Tell method is effective in improving students' speaking skills. The integration of technology not only increased students' confidence but also helped them in aspects of pronunciation accuracy, intonation, diction, sentence structure, and focus on the interlocutor. ABSTRAK Penelitian ini bertujuan untuk meningkatkan kemampuan berbicara siswa kelas IV di SDN 1 Telaga Kabupaten Gorontalo melalui metode Show and Tell berbantuan teknologi. Permasalahan yang dihadapi meliputi kesulitan dalam pengucapan, intonasi datar, pemilihan kata yang kurang tepat, serta kurangnya ekspresi wajah dan kontak mata. Metode ceramah yang dominan menyebabkan siswa jarang berlatih berbicara. Oleh karena itu, integrasi teknologi seperti media interaktif, rekaman video, dan aplikasi pembelajaran digital diterapkan untuk meningkatkan partisipasi siswa. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) dengan teknik pengumpulan data melalui observasi, tes, dan dokumentasi. Subjek penelitian terdiri dari 20 siswa kelas IV. Hasil penelitian menunjukkan bahwa kemampuan berbicara siswa meningkat secara bertahap. Pada observasi awal, hanya 3 siswa (15%) yang memiliki kemampuan berbicara baik. Setelah Siklus I, angka ini meningkat menjadi 50%, dan pada Siklus II mencapai 85%, memenuhi indikator keberhasilan. Kesimpulan penelitian ini menunjukkan bahwa metode Show and Tell berbantuan teknologi efektif dalam meningkatkan kemampuan berbicara siswa. Integrasi teknologi tidak hanya meningkatkan kepercayaan diri siswa, tetapi juga membantu mereka dalam aspek ketepatan lafal, intonasi, diksi, struktur kalimat, dan fokus pada lawan bicara.